INFLUENCE OF PARTICLE SIZE AND PRE-SINTERING TEMPERATURE ON THE PROPERTIES OF ZIRCONIA BLOCK - Amat, N.F.; Muchtar, A.; Abidin, N.F.Z.; Amril, M.S.; Ghazali, M.J.; Yahaya, N.; Aboras, M.M. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This study aimed to evaluate the influence of particle size and pre-sintering temperature on the mechanical properties of pre-sintered monolithic zirconia blocks. Zirconia blocks were fabricated using two types of zirconia 3YSZ powders: one with a particle size of 20-nm (20 nmZ) and another with a particle size of 60-nm (60 nmZ). The blocks were prepared through colloidal processing; shaped through slip casting and cold isostatic pressing; and partially sintered at 850, 900, and 950 °C for 2 h. The 20 nmZ and 60 nmZ blocks had diameters of 40 mm and thicknesses of 5 mm and 20 mm, respectively. Shrinkage, hardness and density properties of the blocks were later examined. The 20 nmZ blocks exhibited higher shrinkage, pre-sintered density, and Vickers hardness than the 60 nmZ blocks. The 20 nmZ blocks exhibited Vickers hardness values that ranged from 0.9 GPa to 1.27 GPa. These values are comparable with that of a commercial product. When sintered at the highest sintering temperature, the 20 nmZ and 60 nmZ blocks achieved 96.5% and 95.9% theoretical density, respectively. Results indicated that the mechanical properties of the pre-sintered monolithic zirconia blocks could be improved by controlling the initial particle size of the parent zirconia powder and pre-sintering the blocks at an appropriate temperature.